A systematic review of coloured environment studies - Ab Jalil, Nurlelawati (Nova Science Publisher, Inc., 2025)
Based on recent developments in colour research, including the introduction of immersive technologies and more sophisticated assessment tools, this chapter refines the thematic categorisation of colour-related studies. The refinement highlights a clearer structure for interpreting the relationship between colour and human responses within the built environment. Five recent studies from 2022 to 2025 have been added, demonstrating how the field has evolved. The revised framework offers valuable insights for researchers and designers seeking to integrate colour more effectively in architectural and interior environments. © 2025 Nova Science Publishers, Inc.